Produksi Tanpa Stok, Akuntansi Tanpa Pencatatan: Ironi Implementasi Akad Istishna (PSAK 404) pada Bisnis Pre-Order UMKM: (Stockless Production, Unrecorded Accounting: The Irony of Istishna Contract (PSAK 404) Implementation in MSMEs' Pre-Order Business) - Wahyu Sarvian Saputra; Oktaviani Putri Ramandhani; Maharani Azizah; Peny Cahaya Azwari (Al-Muhasib: Journal of Islamic Accounting and Finance, 2025)
Abstract: This study examines the implementation of the Istishna' contract (PSAK Sharia 404) in pre-order e-commerce transactions by MSMEs—a rapidly growing business model in Indonesia that lacks comprehensive study from Islamic accounting perspectives. Using a descriptive qualitative approach and a single case study of a food MSME in Palembang, primary data was collected through in-depth interviews and analyzed against PSAK Sharia 404 and DSN-MUI Fatwa No. 06/DSN-MUI/IV/2000. Findings reveal substantive alignment between pre-order practices and core principles of the Istishna' contract regarding: (1) production-on-demand, (2) capital efficiency, and (3) overstock risk mitigation. However, three critical gaps were identified: (a) absence of formal accounting records for revenue/cost recognition, (b) lack of written contracts governing product specifications, delivery schedules, and cancellation mechanisms, and (c) vulnerability in delayed-payment risk management. This research contributes original insights by proposing an adaptation framework for PSAK 404 in MSME e-commerce, emphasizing the urgency of contract digitization, sharia accounting training, and transparency integration in digital business ecosystems. The implications advocate structured mentoring policies to align digital economic practices with Islamic muamalah principles and sharia accounting standards. Abstrak: Penelitian ini menganalisis implementasi akad Istishna' (PSAK Syariah 404) dalam transaksi e-commerce pre-order UMKM—sebuah model bisnis yang berkembang pesat di Indonesia namun minim kajian komprehensif dari perspektif akuntansi syariah. Dengan pendekatan kualitatif deskriptif dan studi kasus tunggal pada pelaku UMKM makanan di Palembang, data primer dikumpulkan melalui wawancara mendalam, kemudian dianalisis melalui perbandingan kriteria PSAK Syariah 404 dan Fatwa DSN-MUI No. 06/DSN-MUI/IV/2000. Temuan mengungkap kesesuaian substantif antara praktik pre-order dengan prinsip dasar akad Istishna' dalam hal: (1) produksi berbasis permintaan, (2) efisiensi modal, dan (3) mitigasi risiko kelebihan stok. Namun, teridentifikasi tiga kesenjangan kritis: (a) absennya pencatatan akuntansi formal untuk pengakuan pendapatan/biaya, (b) tidak adanya kontrak tertulis yang mengatur spesifikasi produk, jadwal pengiriman, dan mekanisme pembatalan, serta (c) kerentanan manajemen risiko pembayaran tertunda. Studi ini memberikan kontribusi orisinal dengan mengusulkan kerangka adaptasi PSAK 404 untuk e-commerce UMKM, menekankan urgensi digitalisasi kontrak, pelatihan akuntansi syariah, dan integrasi prinsip transparency dalam ekosistem bisnis digital. Implikasi penelitian mendorong kebijakan pendampingan terstruktur guna menyelaraskan praktik ekonomi digital dengan prinsip muamalah Islam dan standar akuntansi syariah.